2022
DOI: 10.1038/s41598-022-10676-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in phenology, daily timing of activity, and associations of temperature utilization with survival in three threatened butterflies

Abstract: We used observational data collected during a mark-recapture study that generated a total of 7503 captures of 6108 unique individuals representing three endangered butterfly species to quantify inter-and intraindividual variation in temperature utilization and examine how activity patterns vary according to season, time of day, and ambient temperature. The Marsh Fritillary, the Apollo, and the Large Blue differed in utilized temperatures and phenology. Their daily activity patterns responded differently to tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“… 56 In warm seasons, sunlight and ambient temperature are the main factors influencing butterfly activity, and if conditions are not ideal, butterflies will shift the timing and length of their activity. 57 The diversification of white and yellow butterflies is higher in these environments with stable circadian temperatures. The climatic stability hypothesis 13 predicts that the tropics are especially diverse in part because the climate does not fluctuate much throughout the day or year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 56 In warm seasons, sunlight and ambient temperature are the main factors influencing butterfly activity, and if conditions are not ideal, butterflies will shift the timing and length of their activity. 57 The diversification of white and yellow butterflies is higher in these environments with stable circadian temperatures. The climatic stability hypothesis 13 predicts that the tropics are especially diverse in part because the climate does not fluctuate much throughout the day or year.…”
Section: Discussionmentioning
confidence: 99%
“…However, extremely warm temperatures can reduce activity in some species. 57 Recognizing these trends is crucial in light of the current, unprecedentedly rapid increase in global temperatures during the Anthropocene, particularly our evidence that speciation rates decrease with increasing temperature.…”
Section: Discussionmentioning
confidence: 99%
“…In general, diversity is greater in the tropics, and these areas are often characterized by high temperatures that are generally more constant throughout the year (47). In warm seasons, sunlight and ambient heat are the main factors influencing butterfly activity, and if conditions are not ideal, butterflies will shift the timing and length of their activity (48). The diversification of white and yellow butterflies is higher in these environments with stable circadian temperatures.…”
Section: Diversity Patterns and Temperaturementioning
confidence: 99%
“…Franzén et al (48) found that the survival of the palearctic papilionid Parnassius apollo is negatively affected by increased median temperatures and that there is a tendency for stabilizing selection with temperature in the lycaenid Phengaris arion (48). In general, if temperatures are extreme, behavior and morphology/wing coloration will adapt to regulate body temperature (51)(52)(53)(54).…”
Section: Diversity Patterns and Temperaturementioning
confidence: 99%
See 1 more Smart Citation